Peran Guru Dan Kepala Sekolah Dalam Implementasi Kurikulum Merdeka Belajar - Reisya Diva Maharani Putri; Tannia Alfianti Putri; Asih Andriyati Mardliyah; Sefira Amelia Rosadha; Aditya Nata Widigda (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Culrricullum changes are part of improving the education systelm in Indonesia. This study outlines the role of the principal in implementing the independent curricullum at SD Islam Al Azhar. This study was conducted to investigate thel professionalism of school principals in implementing the independent curricullum. This  type  of  research  is  descriptive  qualitative  using  phenomenological  analysis.  Data  were  collected  by interviewing   school   principals, curricullum representatives, and independent   curricullum implementing teachers.  The  results  showld  that  the  implementation  of  the  independent  curricullum  madel  teachers  more professional through various kinds of coaching and training. Principals carry out their roles as mediators and motivators for teacher participation in curricullum training. The principal also acts as a participant in regullar meetings  or  discussions.  The  principal  is  also  a  supervisor  and  evaluator  in  the  implementation  of  the independent curricullum. The factor faced by the principal is the lack of smooth internet neltwork as a means for teachers to use technology in learning smoothy. The expected results of the theories in the research are taken  into  consideration  by  school  principals  to make  decisions  in  answering  problems  and  improving  the qulality or qulality of eldulcation through the implementation of an independent curricullum.